Perimortem caesarean section – why, when and how. (21st June 2018) - Chu, Justin J; Hinshaw, Kim; Paterson‐Brown, Sara; Johnston, Tracey; Matthews, Margaret; Webb, Julian; Sharpe, Paul
Abstract : Key content: Cardiac arrest in pregnancy is rare. Effective management involves the decision to perform a perimortem caesarean section if the gestation is greater than 20 weeks and return of spontaneous circulation does not occur after 4 minutes of effective cardiopulmonary resuscitation. Delivery should ideally be achieved within 5 minutes of cardiac arrest as this maximises maternal survival and reduces the risk of long‐term neurological impairment. In hospital, the procedure should be undertaken at the site of the cardiac arrest without moving to an operating theatre. Minimal equipment is required to undertake the procedure. Clinical areas where pregnant women are seen should have a designated 'equipment box'. Debriefing all personnel is of utmost importance after the acute event. Learning objectives: To understand why perimortem caesarean section is beneficial to maternal survival. To appreciate the need for rapid decision making when perimortem caesarean section is required. To gain practical knowledge of perimortem caesarean section, including the steps to be used when resuscitation is unsuccessful. Ethical issues: To be aware that the primary aim of perimortem caesarean section is to aid maternal survival, not necessarily fetal survival.